Differential replication of dengue virus serotypes 2 and 3 in coinfections of C6/36 cells and Aedes aegypti mosquitoes - Diana Carolina Quintero-Gil; Marta Ospina; Jorge Emilio Osorio-Benitez; Marlen Martinez-Gutierrez (Journal of Infection in Developing Countries)
Introduction: Different dengue virus (DENV) serotypes have been associated with greater epidemic potential. In turn, the increased frequency in cases of severe forms of dengue has been associated with the cocirculation of several serotypes. Because Colombia is a country with an endemic presence of all four DENV serotypes, the aim of this study was to evaluate the in vivo and in vitro replication of the DENV-2 and DENV-3 strains under individual infection and coinfection conditions. Methodology: C6/36HT cells were infected with the two strains individually or simultaneously (coinfection). Replication capacity was evaluated by RT-qPCR, and the effects on cell viability were assessed with an MTT (3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. Additionally, Aedes aegypti mosquitoes were artificially fed the two strains of each serotype individually or simultaneously. The viral genomes were quantified by RT-qPCR and the survival of the infected mosquitoes was compared to that of uninfected controls. Results: In single infections, three strains significantly affected C6/36HT cell viability, but no significant differences were found in the replication capacities of the strains of the same serotype. In the in vivo infections, mosquito survival was not affected, and no significant differences in replication between strains of the same serotype were found. Finally, in coinfections, serotype 2 replicated with a thousandfold greater efficiency than serotype 3 did both in vitro and in vivo. Conclusions: Due to the cocirculation of serotypes in endemic regions, further studies of coinfections in a natural environment would further an understanding of the transmission dynamics that affect DENV infection epidemiology.